Patient centred care for multimorbidity improves patient experience, but quality of life is unchanged. (15th March 2019) - Cook, Rob; Lamont, Tara; Taft, Rachel
The study: A patient-centred intervention to improve the management of multimorbidity in general practice: the 3D RCT. Salisbury C, Man M-S, Chaplin K, et al. Published in Health Serv Deliv Res 2019;7(5).   This study was funded by the National Institute for Health Research Health Services and Delivery Programme (project number 12/130/15). To read the full NIHR Signal, go to: https://discover.dc.nihr.ac.uk/content/signal-000658/patient-centred-care-for-multimorbidity-improves-patient-experience-but-quality-of-life-is-unchanged